Regenerative capacity of morselized cartilage in vitro and in an osteochondral defect model - Haixiang Liang; Pavit Suri; Matthew I. Saleem; Brian Li; Kenneth Zaslav; Bert R. Mandelbaum; Daniel A. Grande (Elsevier, 2024)
ABSTRACT: Introduction: Numerous treatment modalities for focal articular cartilage defects exist. However, the use of consistent and reproducible minced cartilage morsels to heal these lesions, especially with a scaffold, has not been investigated. Objectives: To investigate the effect of consistently sized minced cartilage morsels on the healing of focal articular cartilage defects. Methods: Cartilage was harvested and morselized into 0.5, 1.0, and 5.0 mm diameters, and cultured. Cell viability and chondrogenic gene expression were analyzed. Minced cartilage morsels of 0.5 mm were harvested and used to produce the implant paste. The NC paste was filled into a rabbit articular cartilage defect, and histology was used to assess cartilage repair. Results: Chondrocyte viability of the morsels was highly maintained. Chondrogenic and proliferative genes like ACAN, COL2, COMP, PCNA, SOX9, and PRG4 all increased expression to a varying degree as morsel size decreased. Morsels of 0.5 mm exhibited the highest chondrogenic potential. Also, NC paste containing 0.5 mm morsels resulted in complete defect closure unlike marrow stimulation alone. Safranin-O staining demonstrated superior cartilage formation in the defect area. Conclusions: Smaller consistent morsel size was found to be linked to increased chondrogenic potential. However, since PRG4 expression was highest in 1 mm morsels and MMP-13 gene expression was significantly decreased in only 0.5 mm morsels, this demonstrates the need to adjust morsel size to optimize gene expression of interest. NC paste mixed with 0.5 mm morsels produced the greatest regenerative capacity. Exploring the regenerative potential of unique hydrogels and chondron morsel sizes is warranted.